FEATURES OF BUSINESS SPORTS AND PHYSICAL EXERCISES STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Khusainov ShamshidinYalgashevic; Kxushvaqtov Usmon Ashurovich; Asrorov Obid Abduvaxobovich (Scholar Express Journals, 2021)
This article is devoted to such a topical topic as the peculiarities of sports and physical exercises among students of higher educational institutions. The article deals with the main motivations of students when choosing sports and systems of physical exercises; about the main reactions of the body to the performed physical work. And also, tests to determine physical fitness.
Keywords: Physical activity; heart rate; motivation; athletic performance